A COPULA APPLICATION FOR MECHANICAL PROPERTIES - Adrian Stere PARIS (Fiabilitate şi Durabilitate)
Based on copula applications, the work points out the use of cumulative distribution function for the characteristics bivariate cases and the connections among them. The analyzed variables, Brinell Hardness and Tensile Strength, are joined in a cumulative distribution function (CDF) to present and forsee the output variable, the copula function. A method using the bivariate density and cumulative distribution function with the Clayton copula, and Gamma distribution is herein analyzed. The dependence between two important mechanical properties is studied and assed.